Wet vs. dry dispersion methods for multiwall carbon nanotubes in the high graphite content phenolic resin composites for use as bipolar plate application - Chaiwan,P. (Elsevier Limited, 2015)
© 2015, Elsevier Ltd. All rights reserved. The preparation of multiwalled carbon nanotubes (MWCNTs) - reinforced graphite/phenolic resin composites is studied. The high electrical conductivity is needed in the composites for the bipolar plates in proton exchange membrane fuel cell (PEMFC) application, so upto 80% by weight of graphite was employed in the composites. The mechanical properties of the composites are found to diminish with this high filler content. The wet and dry nanoparticle dispersion methods are explored in order to disperse MWCNTs in the composites in order to strengthen them. For wet method, MWCNTs are dispersed in 2-propanol via ultrasonication and then mixed with graphite and phenolic resin by dry ball milling. For dry method, all components are mixed only by dry ball milling. After mixing, the composites are fabricated into sheets by hot compression molding. It is found that the dry method is a proper method for preparing composites with high filler content. The composite with 1.0 wt% of MWCNTs prepared by dry method provides highest electrical conductivity and optimum mechanical properties which meets the DOE material requirement for bipolar plates in PEMFC.